Efektivitas Pemberian Air Rebusan Daun Salam dan Daun Kelor terhadap Penurunan Tekanan Darah Pada Lansia Penderita Hipertensi di PMB Eni Lestari, S.Tr.,Keb BEKASI - Apriyana, Diyanti Nur; Jusmawati, Jusmawati (MAHESA : Malahayati Health Student Journal, 2025)
ABSTRACT Lowering blood pressure can be done using herbal therapy, namely by giving boiled water from bay leaves and boiled water from Moringa leaves. Based on the above, the author is interested in conducting research entitled "Effectiveness of Giving Boiled Water from Bay Leaves and Moringa Leaves on Reducing Blood Pressure in the Elderly at PMB Eni Lestari, S.Tr., Keb Bekasi. To determine the effectiveness of giving boiled water from bay leaves and moringa leaves to reduce blood pressure in elderly people suffering from hypertension in the independent practice of midwife Eni Lestari, Str. Keb Bekasi District in 2024. This research uses a Quasy Experiment with a Two Group Pre-test Post-test design. With a purposive sampling technique, there were 30 respondents. The data collection method uses observation sheets. Divided into 2 groups, namely the bay leaf decoction group and the Moringa leaf decoction group. The results of research using the Wilcoxon test and Mann Whitney U test showed that the results of the analysis of bay leaf boiled water had a sig value of systolic ρ-value = 0.000 ≤ α0.05 and diastolic ρ-value = 0.005 ≤ α0.05, meaning that there was an effect of giving boiled water bay leaves to lower blood pressure in elderly people with hypertension. For the analysis of Moringa leaf boiled water, the sig value obtained was systolic ρ-value = 0.001 ≤ α0.05 and diastolic ρ-value = 0.008 ≤ α0.05, meaning that there was an effect of giving Moringa leaf boiled water to lower blood pressure in hypertension sufferers. For the analysis of Moringa leaf boiled water, the sig value obtained was systolic ρ-value = 0.001 ≤ α0.05 and diastolic ρ-value = 0.008 ≤ α0.05, meaning that there was an effect of giving Moringa leaf boiled water to lower blood pressure in hypertension sufferers. S.Tr., Keb Bekasi District. Giving boiled water from bay leaves and Moringa leaves is equally effective in lowering blood pressure, reducing blood pressure in elderly people with hypertension. It is hoped that giving boiled water from bay leaves and Moringa leaves can be used as an alternative treatment to reduce high blood pressure. Drink 1x/day every morning after eating. Keywords: Bay Leaves, Moringa Leaves, Blood Pressure  ABSTRAK Penurunan tekanan darah bisa dilakukan dengan menggunakan terapi herbal yaitu dengan cara pemberian air rebusan daun salam dan air rebusan daun kelor. Berdasarkan hal tersebut diatas maka penulis tertarik melakukan penelitian yang berjudul “Efektivitas Pemberian Air Rebusan Daun Salam Dan Daun Kelor Terhadap Penurunan Tekanan Darah Pada Lansia Di PMB Eni Lestari, S.Tr.,Keb Bekasi. Mengetahui Efektivitas Pemberian Air Rebusan Daun Salam Dan Daun Kelor Terhadap Penurunan Tekanan Darah Pada Lansia Penderita Hipertensi di Praktik Mandiri Bidan Eni Lestari, Str. Keb Bekasi tahun 2024. Penelitian ini menggunakan Quasy Eksperiment dengan desain Two Group Pre-test Post-test desain. Dengan Teknik pengambilam sampel Purposive Sampling sebanyak 30 responden. Metode pengumpulan data menggunakan lembar observasi. Dibagi menjadi 2 kelompok yaitu kelompok rebusan daun salam dan kelompok rebusan daun kelor. Hasil penelitian dengan uji Wilcoxon dan Mann Whitney U Tes didapatkan hasil analisa air rebusan daun salam nilai sig ρ-value sistol = 0,000 ≤ α0,05 dan ρ-value diastol = 0,005 ≤ α0,05, artinya ada pengaruh pemberian air rebusan daun salam untuk menurunkan tekanan darah pada lansia penderita hipertensi. Untuk analisa air rebusan daun kelor diperoleh nilai sig ρ-value sistol = 0,001 ≤ α0,05 dan ρ-value diastol = 0,008 ≤ α0,05, artinya ada pengaruh pemberian air rebusan daun kelor untuk menurunkan tekanan darah pada penderita hipertensi. Hasil analisis Mann Whitney diperoleh nilai sig ρ-value sistol = 0,775 ≥ α0,05 dan ρ-value diastol = 0,732 ≥ α0,05, artinya tidak ada perubahan rebusan daun salam dan daun kelor terhadap penurunan tekanan darah pada lansia penderita hipertensi di PMB Eni Lestari, S.Tr.,Keb Bekasi. Pemberian air rebusan daun salam dan daun kelor sama-sama efektif dalam menurunkan tekanan darah, penurunan tekanan darah pada lansia penderita hipertensi. Diharapkan pemberian air rebusan daun salam dan daun kelor dapat dijadikan sebagai pengobatan alternatif untuk menurunkan tekanan darah tinggi. Diminum 1x/hari setiap pagi setelah makan. Kata Kunci: Daun Salam, Daun Kelor, Tekanan Darah